Myth as a Revelation of Spiritual Values for Today’s Human Life Reflected on Sarah H. Bradford’s "Harriet Tubman: The Moses of Her People" - Triana, Ike Alit; Yulianto, Henrikus Joko (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
America is a country with Christianity as the major religion. It is the fact that Moses in Christian myth has an important role to the religion of this country. The United States President Harry Truman wrote in 1950 that the fundamental basis of the laws of the United States was the Ten Commandments that were given to Moses. America is also known for the country of freedom. Besides, American freedom has a unique historical story which is about slavery. Harriet Tubman: The Moses of Her People novel depicts the journey and struggle of Harriet in liberating African American slaves. This study aims to identify the incorporation of Moses in Christian myth to the story in the novel and its relation to the spiritual values of humanÃ¢â‚¬â„¢s life in the present time. The method of this study is qualitative study analysis using structuralism method of Claude Levi Strauss and the Study of Myth by Joseph Campbell. Then, the method of data analysis is based on the story in Harriet Tubman: The Moses of Her People novel and Moses in Christian myth. BradfordÃ¢â‚¬â„¢s novel tells about the main character named Harriet who became the leader of African American slaves to the Northern America and Canada for freedom. While in Christian myth, Moses was chosen by God to be the leader of Israelites to go from the land of Egypt bondage for freedom. The final finding of this study shows the conflict of the novel, the incorporation of Moses in Christian myth to the story in the novel and shows the Ten Commandments of Christianity influenced the spiritual values by Americans which is also still relevant today. For instance, most Americans are Christian as the values of the First Commandment; Americans commonly regard their society as the freest and best in the world as the value of the Eight Commandment; the right of American constitutional democracy to attempt to Ã¢â‚¬Å“pursueÃ¢â‚¬Â happiness in their own way as long as they do not infringe upon the rights of others is a result of the Tenth Commandment; Although there are still some transgressions of one or more of the Commandments, there are somehow many other Americans who are still devoted to the Ten Commandments as moral principles in their daily life. Keywords: African-American, Christian myth, Moses, Slavery, Structuralism